The Effect of Leverage on Firm Growth - Tuominen, Jesse (My University, 2015)
The choice of capital structure is one of the most dominant decisions that define the financial state of a firm. Modigliani and Miller (1958) state that capital structure is irrelevant, but the financial conditions required for this statement are not met in the real world. Different capital structure theories have been presented but there is no consensus of which of these theories could be considered as a norm. This complicates the investigation of capital structure’s effects on firm operations. One big issue is how leverage affects the firm’s investments and growth. The purpose of this study is to contribute to the discussion of the effect of leverage on firm growth measured in capital expenditures and changes in employment. Furthermore, whether the firm's growth opportunities affect this relationship. This research also closely concentrates on the financial crisis and how that has affected the relationship between leverage and firm growth. The data in this research consist of listed U.S. companies from 2002-2013 with at least one billion dollar sales measured in 2002 dollars. Growth is measured with capital expenditures growth, employment growth and net investment growth. Multiple linear regressions with White adjusted standard errors are estimated for three time periods: whole period of 2002-2013, normal period of 2002-2006 and 2011-2013 combined, and abnormal period of 2007-2010. This is done to test if the financial crisis has affected the relation between leverage and firm growth. The regressions are also conducted for subgroups defined by Tobin’s q to examine if the firms’ growth opportunities affect the relation between capital structure and growth. The results show that in normal economical times, leverage is negatively associated with firm growth. However, this relation is stronger for firms with poor growth opportunities. During economical downturn, leverage has a strong negative relation with growth for firms with poor growth opportunities, but not for other firms. The results provide evidence for that leverage is negatively associated with firm growth particularly for firms with low growth opportunities and that economical downturn strengthens this relation for firms with poor growth opportunities and eliminates it for firms with high growth opportunities.
Keywords: capital structure; growth; leverage; investment; subprime crisis; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|